Шествие: иллюзия и реальность в иррациональном пространстве (к проблеме иконографии и композиции в древнем искусстве) - Королькова, Е.Ф. (Археологія і давня історія України, 2019)
Статья посвящена проблеме классификации
иконографических и композиционных типов в памятниках древнего искусства, в частности, так
называемых «шествий», которые связаны с изобразительным оформлением сферы особого семантического значения. Будучи расположенными на
предметах, относящихся к категории персональных украшений и оружия, на монументальных памятниках или предметах самого разнообразного
назначения, они всегда, так или иначе, сопряжены
с сакральными действиями, мифологическим пространством и ритуалом. Понимание их содержания невозможно без первичной классификации, которая до сих пор не разработана, что приводит к трудностям в исследованиях. The article is devoted to the problem of classification
of iconographic and compositional types in the
monuments of ancient art, in particular, the so-called
«processions», which are associated with the artistic
design of the objects belonging to the sphere of great
semantic meaning. Being located on objects of the category
of personal adornments and weapons, on architectural
monuments or ritual objects, they are always
associated with sacred acts, mythological space and
ritual content. Interpretation of these compositions is
impossible without a primary classification, which has
not yet been developed, and this causes difficulties in
research.
Compositions, which could be concerned as processions
could consist of anthropomorphic or zoomorphic
images, or comprise both type of images in the same
composition. All of them always show some rhythmical
characteristics with constant intervals as well as
evident direction of movement.
In some occasions such type of compositions could
be taken as an embodiment of the scene of a concrete
ritual event, sometimes, perhaps, with costumed as
mythological personage figures, but in other case they
could be interpreted as a mythological subject with
well-known images, which were recognizable for ancient
society. In any case reiteration of images and
regular intervals in compositions made an impression
of slow movement in solemn procession, even with statical
figures.